Introducing geomorphology : a guide to landforms and process - Harvey, Adrian (Dunedin, 2013)
Geomorphology is the study of the earthÕs landforms and the processes that made the landscape look the way it does today. What we see when we look at a scenic view is the result of the interplay of the forces that shape the earthÕs surface. These operate on many different timescales and involve geological as well as climatic forces. Adrian Harvey introduces the varying geomorphological forces and differing timescales which thus combine: from the global, which shape continents and mountain ranges; through the regional, producing hills and river basins; to the local, forming beaches, glaciers and slopes; to those micro scale forces which weather rock faces and produce sediment. Finally, he considers the effect that humans have had on the worldÕs topography. Introducing Geomorphology provides a structured and easily accessible introduction to the science of geomorphology for those with an adult curiosity about the landscape and for those contemplating a course of formal study in physical geography, geology or environmental studies. As with sister volumes, technical terms are kept to a minimum and a glossary is provided.